Analisis Faktor-Faktor Yang Mempengaruhi Akuntabilitas Kinerja Instansi Pemerintah - Febrianti, Tania; Indrawati Yuhertiana (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2021)
This study aimed to examine and analyze the effect of implementation of perfomarmance-based budgeting, budget target accuracy and compliance with laws and regulations to performance accountability of government agencies. This research uses quantitative research using primary data. The primary data is a questionnaire that has been distributed to 97 respondents in Regional Device of Surabaya City Government. The data analysis technique used in this research is PLS-SEM with the help of SmartPLS version 3.0 for windows software. The results of the study prove that the variables of implementation of perfomarmance-based budgeting, budget target accuracy and compliance with laws and regulations had positive effect on performance accountability of government agencies. In other words, its Regional Device located in Surabaya City Government had good governance with good accountability as the realization of well budget and internal supervison.